Spatial fragmentation as an opportunity for resilience building through urban acupuncture: Learning from Tehran and Bucharest - Naghibi Maryam; Forgaci Claudiu; Faizi Mohsen (Lodz University of Technology Press, 2023)
The rapid urbanization of metropolitan environments worldwide has led to increasing spatial fragmentation. Disconnected spaces have revealed spatial and social voids that reduce the adaptive capacity of a region. However, these spaces also offer latent potential for urban resilience. Accordingly, this study reveals how urban acupuncture promotes resilience in leftover spaces to reduce or embrace spatial fragmentation. This paper reviews spatial fragmentation and urban resilience from descriptive-analytical and normative perspectives. It proposes urban acupuncture to locate critical spatial structures and processes on a small scale. The study develops a conceptual framework around fragmentation and urban acupuncture. It investigates the assumptions behind the concepts of spatial fragmentation and proposes a dialectical framing of vacancy based on resilience and urban acupuncture, along with a reassessment of leftover space as a planning tool. The framework’s application is demonstrated in Tehran and Bucharest. As a result, spatial fragmentation significantly influences urban resilience to prevent expansion. Urban acupuncture opens the possibility of developing optimistic scenarios by considering leftover spaces and the broader opportunities they generate for urban resilience. Depending on the urban context, this strategy can be applied through a single intervention in a specific place or a network of coordinated interventions in different locations.
Keywords: spatial fragmentation; leftover space; resilience; urban acupuncture; fragmentacja przestrzenna; resztki przestrzeni; odporność; akupunktura miejska